Stability of New Anticancer Agents in Intravenous Solutions - Cielecka-Piontek, Judyta; Jelinska, Anna; Dolhan, Agnieszka; Zalewski, Przemyslaw; Burek, Darek; Piekarski, Mikolaj; Krause, Anna; Uszak, Justyna; Oszczapowicz, Irena; Lukawska, Malgorzata (Asian Journal of Chemistry, 2011)
The purpose of this study is to determine the stability of daunorubicin derivative containing in the amidine group a piperidine (DD-1), morpholine (DD-2), pyrrolidine (DD-3) or hexahydroazepine (DD-4) moiety in intravenous solutions. For DD-2, the influence of its concentration and of the light-protective effect of packaging on the stability of that compound was also investigated. The influence of intravenous solutions and conditions of storage on the stability of new derivatives of daunorubicin was studied by HPLC method. After storage at room temperature DD-3 was the most stable (in 84.6 % of the intravenous solutions) whereas the DD-2 was stable only in two of the solutions over a study period of 2 h (5 % glucose and 0.9 % NaCl). When stored at 2-6 ºC all derivatives of daunorubicine in the intravenous solutions were more stable. The unfreezing of the intravenous solutions to room temperature caused additional degradation. The concentration of DD-2 did not have any significant influence on the rate and kinetic mechanism of degradation. Exposure to light also did not have any significant effect on the degradation of DD-2 when it was stored in polypropylene syringes.